1990
DOI: 10.3171/jns.1990.73.1.0003
|View full text |Cite
|
Sign up to set email alerts
|

Total removal of craniopharyngiomas

Abstract: The clinical features, perioperative course, and postoperative outcomes of 144 patients who underwent microsurgical resection of craniopharyngioma were reviewed. Overall, 90% of the tumors were completely resected and 7% recurred. Evaluation of those patients who underwent primary resection revealed much better results. The operative techniques and approaches are reviewed in detail. The results of this series suggest that primary total removal of craniopharyngiomas yields the best long-term outcome for the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
165
2
5

Year Published

1999
1999
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 727 publications
(175 citation statements)
references
References 22 publications
3
165
2
5
Order By: Relevance
“…It is not clear whether the presence of HY constitutes a prognostic factor because both increased mortality (12) and lack of association with mortality have been reported (13,14,15,16). Our retrospective analyses of the thus far largest published cohort of long-term survivors of childhood-onset CP and CRP show that HY at diagnosis was not associated with reduced survival rates and impaired FC during long-term follow-up, supporting previous reports (13,14,15,16).…”
Section: European Journal Of Endocrinologysupporting
confidence: 71%
See 4 more Smart Citations
“…It is not clear whether the presence of HY constitutes a prognostic factor because both increased mortality (12) and lack of association with mortality have been reported (13,14,15,16). Our retrospective analyses of the thus far largest published cohort of long-term survivors of childhood-onset CP and CRP show that HY at diagnosis was not associated with reduced survival rates and impaired FC during long-term follow-up, supporting previous reports (13,14,15,16).…”
Section: European Journal Of Endocrinologysupporting
confidence: 71%
“…What remains unclear is whether the age at diagnosis represents a survival prognostic factor because some studies have demonstrated that the youngest patients have better survival rates (28,32,44), others have found better outcome in older patients (12,46), whereas still other studies report no difference between pediatric and adult populations (13,16,45,47). The role of sex as a prognostic factor is not established; some authors report a higher mortality among females (28,29), but others have not found any sex differences (13,15,16).…”
Section: European Journal Of Endocrinologymentioning
confidence: 84%
See 3 more Smart Citations